Evaluating the effect of daylength (24, 20, and 18 hours) during brooding on broiler performance and physiological responses to light environment - Garret G. Ashabranner; Michael Czarick, III; Brian D. Fairchild (Journal of Applied Poultry Research)
Summary: Brooding broiler chicks under continuous or near-continuous light is common in poultry research and commercial poultry production. Despite its prevalence, there is a notable lack of research to support its use. The current research investigated the impact of various daylengths (24, 20, and 18 hours) during brooding on broiler performance and physiological responses to the light environment. Broiler performance and physiological responses were assessed in four experiments comprised of ten trials. Control birds reared under continuous light during brooding initially exhibited higher body weight during the first week (P ≤ 0.05). Following the introduction of the dark period for the control groups on Day 7, the treatment birds subjected to dark periods during brooding overtook the control group in body weight. From Days 28-42, no differences in performance were observed between the control and treatment groups. No significant differences were found in feed conversion between treatment and control groups during any experiment. Corticosterone and superoxide dismutase were consistently unaffected by either lighting program. The introduction of a dark period during brooding led to higher baseline and nighttime elevation in melatonin levels in the treatment birds, persisting up to 35 days of age. Field trials conducted in commercial poultry houses further confirmed the research's findings, with no significant differences observed in performance or mortality when compared to control and treatment houses. This research illustrates that providing broiler chicks with a dark period from day of placement does not have detrimental effects on end-of-flock performance.